Assessing the role of oceanic heat fluxes on ice ablation of the central Chukchi Sea Shelf. (May 2020) - Lu, Kofan; Danielson, Seth; Hedstrom, Katherine; Weingartner, Thomas
Highlights: Frontal baroclinic regulate the quantity of heat fluxed to the ablating ice edge. Bering Strait inflow is critical in initiating ice retreat by melting and northward advection. Bering Strait inflow is responsible for the bulk of the ~10 TW of heat in summer in our model. Eddies carrying heat from the Bering Strait provide ~30% of the total oceanic heat. Vertical eddy transport supplies >30% of the total heat content variation to surface. Abstract: We investigate the role of oceanic heat flux convergence in the summertime retreat of sea ice in the presence of a mean background flow. Prior studies indicated that eddies generated along the marginal ice zone front carry substantial quantities of heat laterally beneath the ice, but the direct importance of these fluxes to the summertime retreat of sea ice was not well established. We use the Regional Ocean Model System (ROMS) with an idealized configuration of the Chukchi Sea shelf and without wind forcing to: (1) determine the contributions to ice melt from the oceanic heat flux compared to that from the net atmospheric heat flux through the ice surface; (2) evaluate the role of mesoscale fluctuations versus the mean background flow in providing this sub-surface heat flux, and (3) evaluate the role of the underlying bathymetry in modifying the subsurface heat flux to the ice. Analyses show that the three main water masses (Melt Water, Bering Sea Water and Winter Water) establish frontal systems (the Shelf Water Front and the Ice Edge Melt Water Front) that control baroclinic processes, which in turn regulate the quantity of heat fluxed laterally and vertically to the ablating ice edge. We identify and characterize distinct oceanic zones associated with these fronts (the Shelf Water Transition Zone and the Melt Water Transition Zone) that are delineated by flow dynamics and hydrographic structure. The integrated heat flux along the modeled ice edge is significant: lateral eddy transport of heat is as large as 2 TW, of which 50% is fluxed upwards into the near-surface Melt Water. We introduce a parameterization for the vertical heat transport to the ice through the near-surface meltwater lens that is a function of the along-front current velocity and the cross-front temperature gradient. Such a parameterization could improve coarse-scale ocean and climate models that lack the resolution necessary for reproducing such small-scale processes. The results of this study may be informative to investigations of ice edge biological processes.